Bibliometric and visual analysis of immunisation associated with acute kidney injury from 2003 to 2023 - Chen, Ling; Hu, Jing; Lu, Jianrao; Gong, Xuezhong (Frontiers in Pharmacology, 2024)
Objective: This study aims to conduct a detailed bibliometric and visual analysis of acute kidney injury (AKI) and immune-related research conducted over the past two decades, focusing on identifying emerging trends and key areas of interest. Methods: The Web of Science Core Collection (WoSCC) was utilised for the meticulous examination of various parameters including publication volume, authorship, geographic distribution, institutional contributions, journal sources, prevalent keywords and citation frequencies. Data were intricately visualised and interpreted using VOSviewer, CiteSpace and Excel 365 software. Results: Analysis of the WoSCC database revealed 3,537 articles on AKI and immunisation, originating from 94 countries and regions, involving 3,552 institutions and authored by 18,243 individuals. Notably, the top five countries contributing to this field were the United States, China, Germany, Italy and the United Kingdom, with the United States leading with 35.76% of total publications. Among the 3,552 contributing institutions, those in the United States were predominant, with Harvard University leading with 134 papers and 3,906 citations. Key journals driving productivity included Frontiers in Immunology, Kidney International, Journal of the American Society of Nephrology and International Journal of Molecular Sciences, with Kidney International being the most cited, followed by Journal of the American Society of Nephrology and New England Journal of Medicine. Prominent authors in the field included Ronco Claudio, Okusa Mark D and Anders, Hans-Joachim. Co-citation clustering and timeline analysis highlighted recent research foci such as Covid-19, immune checkpoint inhibitors, regulated necrosis, cirrhosis and AKI. Keyword analysis identified 'inflammation', ' ischaemia-reperfusion injury ','sepsis', 'covid-19 ',and ' oxidative stress ' as prevalent terms. Conclusions: This study provides the first bibliometric analysis of AKI and immune research, offering a comprehensive overview of research hotspots and evolving trends within the field.